Eight principles of neuro-inclusion; an autistic perspective on innovating inclusive research methods - Dark, Jessica (Frontiers in Psychology, 2024)
In this article I explain the value of autistic perspectives in research and argue that support for autistic scholars, community leaders and professionals are required as an inclusive research consideration. I propose consolidation, innovation, and evaluation of inclusive research principles, with consideration given to epistemic agency, autistic participation, and actionable research outcomes. I then present ‘Eight Principles of Neuro-Inclusion’, a reflexive tool that I have designed as a way of encouraging new developments of inclusive research practices. Through flexible application of this approach, it is hoped that innovative new inclusive methods will materialise, in pursuit of epistemic justice, and in support of actionable research outcomes that benefit our autism community.